2015
DOI: 10.1177/0956797614567339
|View full text |Cite
|
Sign up to set email alerts
|

When Does Cognitive Functioning Peak? The Asynchronous Rise and Fall of Different Cognitive Abilities Across the Life Span

Abstract: Understanding how and when cognitive change occurs over the lifespan is a prerequisite for understanding normal and abnormal development and aging. Most studies of cognitive change are constrained, however, in their ability to detect subtle, but theoretically informative lifespan changes, as they rely on either comparing broad age groups or sparse sampling across the age range. Here, we present convergent evidence from 48,537 Web participants and a comprehensive analysis of normative data from standardized IQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
480
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(537 citation statements)
references
References 41 publications
49
480
1
7
Order By: Relevance
“…That is, even if questions were well understood, the 30-50 year old respondents showed greater difficulty with keeping the question in mind while forming a relevant response. This finding is in line with recent systematic investigations of the age of peak performance across different cognitive tasks: Hartshorne and Germine (2015) found in a series of experiments that processing speed peaks around age 20, working memory around age 30, and comprehension/vocabulary around age 50. Eur J Ageing (2016) 13:185-193 189 Thus, what people report is affected by what information they can remember and retrieve from memory and how easy or difficult the question format renders this cognitive task.…”
Section: Retrieving Relevant Information From Memory and Making A Judsupporting
confidence: 92%
“…That is, even if questions were well understood, the 30-50 year old respondents showed greater difficulty with keeping the question in mind while forming a relevant response. This finding is in line with recent systematic investigations of the age of peak performance across different cognitive tasks: Hartshorne and Germine (2015) found in a series of experiments that processing speed peaks around age 20, working memory around age 30, and comprehension/vocabulary around age 50. Eur J Ageing (2016) 13:185-193 189 Thus, what people report is affected by what information they can remember and retrieve from memory and how easy or difficult the question format renders this cognitive task.…”
Section: Retrieving Relevant Information From Memory and Making A Judsupporting
confidence: 92%
“…The links between the established visual processing declines in face recognition and the declines as we age in recognition of some of the emotions portrayed in faces need further study; one of our studies linking these elements is to be reported in due course. Regardless, further research on psychological and neurological bases associated with what we see or do not see as we age continues apace (cf., Barulli & Stern, 2013;Hartshorne & Germine, 2015;Konar, Bennet, & Sekular, 2013;Salthouse, 2012;Utz & Carbon, 2016). Increasing understanding of the processes should help bring about more effective treatment, and exercise and educational programs that help reduce the effects of errors in our face recognition processes and hopefully add to the quality of our lives as we age.…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous studies on mild and more severe cognitive decline as we age, because of the importance in dealing with non-normal decline such as in Alzheimers' disease and generally aiming to identify what was occurring and to assist in alleviation of normal or mild cognitive decline or impairment (e.g., Agrigoroaei & Lachman, 2011;Albert et al, 2011;Hartshorne & Germine, 2015;Luchetti et al, 2014;Palop & ijps.ccsenet.org International Journal of Psychological Studies Vol. 9, No.…”
Section: Age and Visual Processing And Mild Cognitive Declinementioning
confidence: 99%
“…These alterations may be associated several neuro cognitive changes differing in severity. In fact, there is considerable variability in the age at which cognitive abilities peak and decline throughout life [15].…”
Section: Cellular and Sub-cellular Alterationsmentioning
confidence: 99%